2019
DOI: 10.1108/ijmhsc-05-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Migrant women’s health and housing insecurity: an intersectional analysis

Abstract: Purpose This paper presents an analysis of how health intersects with the experience of housing insecurity and homelessness, specifically for migrant women. The authors argue that it is important to understand the specificities of the interplay of these different factors to continue the advancement of our understanding and practice as advocates for health and housing security. Design/methodology/approach An exploratory, qualitative, methodological approach was adopted, using a broad definition of housing ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
(72 reference statements)
0
18
0
Order By: Relevance
“…Focusing specifically on culture or gender would result in a singular view of the newcomer mother experience of homelessness. Other qualitative work in this area highlights the need to examine the intersectional factors of both migration and gender, which combine to affect the vulnerability of newcomer women to housing instability and homelessness [70]. Our approach recognizes the "disadvantage of immigrant women in relation to the dynamics of violence: ethnicity, immigrant status, and interacting gender inequalities" [71], (p. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing specifically on culture or gender would result in a singular view of the newcomer mother experience of homelessness. Other qualitative work in this area highlights the need to examine the intersectional factors of both migration and gender, which combine to affect the vulnerability of newcomer women to housing instability and homelessness [70]. Our approach recognizes the "disadvantage of immigrant women in relation to the dynamics of violence: ethnicity, immigrant status, and interacting gender inequalities" [71], (p. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Stigma against women experiencing violence is commonly exemplified by "not in my backyard" campaigns against transition houses or by property owners who assume renting to these women will lead to property damage and violence in their neighborhoods (Knowles et al, 2019). Intersectionality matters here: immigrants, Indigenous, women of color, women with children, and those who are LGBTQ2+ report high levels of discrimination in housing searches on the private market, and are also more likely to be evicted (Addis et al, 2009;Hanley et al, 2019;Martin & Walia, 2019;Teixeira, 2006Teixeira, &, 2008Quets et al, 2016).…”
Section: Discrimination Eviction and Coercionmentioning
confidence: 99%
“…Wood & Kallestrup (2018) and Polillo et al (2018) studies revealed employment status and the quality of health as considerations for migrating. Gender and employment status are also interesting variables to be analyzed in explaining individual considerations to migrate as new information in analyzing migration compared to previous studies (Hanley et al, 2019;Hollis, 2019;Maleku, Kim, & Lee, 2019). The studies revealed that gender differences affected individual decisions in migrating, whether there were specific considerations between men and women in determining the decision to migrate or not.…”
Section: Introductionmentioning
confidence: 99%
“…(Adams in Indonesia is an interesting part of this study compared to previous research on migration in developing countries. Hanley et al (2019) have researched the health aspects of female migrants and household safety as research variables on migration but did not include aspects of marital status, income level, and education status. Wood & Kallestrup (2018) and Polillo et al (2018) studies revealed employment status and the quality of health as considerations for migrating.…”
Section: Introductionmentioning
confidence: 99%